Pengaruh Model Numbered Heads Together Berbantuan Media Canva Terhadap Hasil Belajar Dan Keterampilan Komunikasi Siswa - Nashiruddin Nashiruddin; Nana Sepriyanti; Misra Misra (Institut Agama Islam Sumatera Barat, 2024)
This research was motivated by the low learning outcomes and communication skills of students, this can be seen from the mid semester 1 grades of class XII at SMAN 5 Padang for the 2023/2024 academic year. The solution to overcome this is to use the Numbered Heads Together Model assisted by Canva Media for Student Learning Outcomes and Communication Skills in PAI Learning. The formulation of the problem in the research is: (1) Are there differences in PAI learning outcomes between students taught using the Numbered Heads Together model assisted by Canva media with direct learning (2) Are there differences in the communication skills of students taught using the Numbered Heads Together model assisted by Canva media with Direct Learning (3) Is there an influence of student communication skills on learning outcomes in PAI learning. This type of research is a quasi-experiment (Quasy Experiment). The population in this study was 396 students in class XII SMA N 5 Padang for the 2023/2024 odd semester academic year. The sampling in this research was Random Sampling, the classes selected as experimental classes were class XII MIPA 1 and control class XII MIPA 2. The research results show: (1) There is a significant difference in learning outcomes between students taught using the Numbered Heads Together Model assisted by Canva Media and direct learning. By calculation, Tcount = 9.823 is greater than Ttable = 1.666 with a significance level of 0.000 < 0.05. (2) There is a significant difference in the results of students' communication skills taught using the Numbered Heads Together Model assisted by Canva Media and direct learning. By calculation, Tcount = 7.191 is greater than Ttable = 1.666, with a significance level of 0.000 < 0.05. (3) There is a significant influence between students' communication skills on learning outcomes in PAI learning. With supporting data, Fcount = 9,647 is greater than Ftable = 4,139 at the significance level α = 0.05. Key words: Numbered Heads Together Model assisted by Canva Media, student learning outcomes, student communication skills.